ANALISIS KEANDALAN KOMPONEN KRITIS LIFT NPX-36000 UNTUK MENENTUKAN JADWAL PERAWATAN PENCEGAHAN YANG OPTIMUM - Ras, Sachbudi Abbas; Setiawan, Andy (Industrial and Systems Engineering Assessment Journal (INASEA), 2006)
Maintenance system, surely takes important role for daily operational lift. A lift which frequently broken could delay the activities. The right maintenance system should be the one that is planned well. If we could identify or estimate an elevator reliability level, then we could determine when should the maintenance, in form of part replacement, best to perform. The data shown that lift NPX-36000 is the critical lift and its critical part is PCB, because of PCB failure percentage is more than 50% from all failure.